2015
DOI: 10.1002/2015jf003685
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic analysis of fully developed turbidity currents over plane beds based on self‐preserving velocity and concentration distributions

Abstract: This paper presents a hydrodynamic analysis for the fully developed turbidity currents over a plane bed stemming from the classical three‐equation model (depth‐averaged fluid continuity, sediment continuity, and fluid momentum equations). The streamwise velocity and the concentration distributions preserve self‐similarity characteristics and are expressed as single functions of vertical distance over the turbidity current layer. Using the experimental data of turbidity and salinity currents, the undetermined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…2a ). This characteristic form of vertical velocity profiles is well-fitted by earlier empirical models developed for dilute turbidity currents 33 , 34 . Integrating these studies on particle-laden gravity currents with recent studies on volcanic plumes 35 , 36 , we here propose a continuous power-Gaussian mathematical form of the mean vertical velocity profile as where the dimensionless height , with being the height of the wall region where the velocity maximum occurs; is the wall layer exponent; is the jet region exponent; and where and are fitted variables.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…2a ). This characteristic form of vertical velocity profiles is well-fitted by earlier empirical models developed for dilute turbidity currents 33 , 34 . Integrating these studies on particle-laden gravity currents with recent studies on volcanic plumes 35 , 36 , we here propose a continuous power-Gaussian mathematical form of the mean vertical velocity profile as where the dimensionless height , with being the height of the wall region where the velocity maximum occurs; is the wall layer exponent; is the jet region exponent; and where and are fitted variables.…”
Section: Resultssupporting
confidence: 75%
“…2b ). In the jet region, the density profiles are well described by current empirical models developed for dilute gravity currents 34 . However, in the wall region, vertical density gradients are strongly enhanced due to the fast settling of mesoscale turbulent particle clusters 32 , 37 , 38 and neither instantaneous nor time-integrated concentration profiles are well described by existing empirical models 34 .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We simplify both the temperature and mass fraction profiles by neglecting their temporal variability, and give their time-average profile. Data are fitted with the theoretical exponential profile proposed by Cantero-Chinchilla et al (2015) for 3) and the parameters reported in legend and in Tab. 6.…”
Section: The Theoretical Model For Temperature and Concentrationmentioning
confidence: 99%